Endometrial Cancer-Infiltrating Mesenchymal Stem Cells Exhibit Immunosuppressive Effects - Kai-Hung Wang; Yu-Hsun Chang; Tomor Harnod; Dah-Ching Ding (Cell Transplantation, 2022)
Endometrial cancer is the most common gynecologic cancer with high heterogeneity. However, there are limited treatment options for advanced endometrial carcinoma. In recent years, immunotherapy has broadly been used for the treatment of various cancers. However, the efficacy of immunotherapy against endometrial cancer is limited. The tumor microenvironment, including mesenchymal stem cells (MSCs), may contribute to tumor progression through cancer cells themselves and through cells of the immune system. We successfully isolated endometrial cancer–derived MSCs (EmCaMSCs) from patients and found that the population of MSCs in tumor tissues was approximately 1%–5%. The population of MSCs correlated with the stage of the disease. EmCaMSCs expressed MSC markers and exhibited trilineage differentiation ability. The programmed death ligands PD-L1 and PD-L2 were highly expressed in EmCaMSCs; their expression could be further enhanced by tumor necrosis factor-α and interferon-γ. When cocultured with peripheral blood mononuclear cells (PBMCs), anti-CD3, and anti-CD28, EmCaMSCs inhibited the proliferation of PBMCs, which were partially rescued by treatment with anti-PD-L1 antibodies. From the profile of conditioned medium of EmCaMSCs, we discovered that interleukin (IL)-8 and insulin-like growth factor–binding protein 6 could also rescue the proliferation of PBMCs. Furthermore, EmCaMSCs cocultured with IL-2-induced PBMCs exhibited decreased expression of CD56, CD4, and CD8 and showed decreased cytotoxicity toward K562 cells and endometrial cancer cells. Overall, EmCaMSCs were isolated successfully from endometrial cancer tissues and exhibited immunosuppressive effects and may be targeted for the treatment of endometrial cancer by anti-cytokine and immune checkpoint inhibitors. The percentage of MSCs in tumor stroma might predict the prognosis of endometrial cancer.